Current Issues in Sport Science - Claudio Nigg; Markus Tilp; Günter Amesberger; Carol Ewing Garber; Thomas Finkenzeller; Martin Keller; Christine Pellegrini; Sebastian Ruin; Thorsten Stein; Ansgar Thiel; Mireille van Poppel; Sabine Würth (Bern Open Publishing, 2022)
CISS welcomes and encourages articles addressing a broad range of topics across sport science which include but is not limited to genetic, biological, physical, physiological, psychological, pedagogical, sociological, environmental, policy among other aspects. In this editorial, we highlight several topics of interest for each of our sections within CISS: biology & medicine, biomechanics & informatics, movement & exercise science, pedagogy & history, psychology & philosophy, public health, sociology & economics and technology. We hope to motivate you and your colleagues to join us in advancing the field of sport science.